Public Perception of Environmental Pollution in Warri, Nigeria - AA Obafemi; OS Eludoyin; BM Akinbosola (Journal of Applied Sciences and Environmental Management)
The study assessed the public perception on the environmental pollution profile in Warri Township. Data were acquired by administering questionnaire among the residents of study area using random sampling method and descriptive statistics was used to explain the frequencies of variables being expressed in percentages. The result of the analysis showed that 72.4% of total respondents affirmed that air pollution was greatest among other types of pollution while the major source of pollution was oil spillage and gas flaring and there is no time that pollution cannot occur as 52.6% of respondents agreed on this. Environmental resources were believed to be partially and totally damaged suggesting that the degree of pollution was high. Furthermore, 26.4% and 14.5% of respondents believed that water pollution leads to loss of aquatic lives and reduction of potable water. Cough disease was believed to be really affecting the entire people of the area as 19.7% and 44.7% of total respondents agreed that water pollution and air pollution respectively caused the disease. However, 96.1% had the opinion that soil pollution caused stunted growth of plants. The study therefore suggested among others that government should promulgate and enforce environmental laws that will reduce the level of pollution in the area, planting of trees should be encourage, gas flaring should be stopped and adequate facilities of transporting petroleum products should be put in place.